2016
DOI: 10.1016/j.engfracmech.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A virtual crack extension method to compute energy release rates using a complex variable finite element method

Abstract: The complex-valued finite element method, ZFEM, is proposed as a new virtual crack extension method to compute the energy release rate. The energy release rate is computed as a numerical derivative of the strain energy with respect to a crack extension using the complex Taylor series expansion method (CTSE). This is accomplished using a finite element method with complex nodal coordinates and extending the crack by a very small quantity along the imaginary directions of the complex nodal coordinates. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…The results showed that on average, ZFEM required 45% less total CPU time to solve the Transient Thermal ZFEM model and obtain sensitivities compared to using built-in Abaqus functions and FD. This contrasts with that reported in the ZFEM literature for more complicated physics, where 2.5 to 4 times longer computational times were obtained for equivalent real variable runs [71,74,87]. This behavior shows another advantage of using CTSE for thermal linear problem as it requires only one evaluation of model to obtain sensitivities.…”
Section: Computational Efficiency Of Transient Thermal Zfemcontrasting
confidence: 68%
See 2 more Smart Citations
“…The results showed that on average, ZFEM required 45% less total CPU time to solve the Transient Thermal ZFEM model and obtain sensitivities compared to using built-in Abaqus functions and FD. This contrasts with that reported in the ZFEM literature for more complicated physics, where 2.5 to 4 times longer computational times were obtained for equivalent real variable runs [71,74,87]. This behavior shows another advantage of using CTSE for thermal linear problem as it requires only one evaluation of model to obtain sensitivities.…”
Section: Computational Efficiency Of Transient Thermal Zfemcontrasting
confidence: 68%
“…Fins are present in almost all heat transfer applications such as engines, computers and electronics, and cooling systems. It is worth highlighting that ZFEM has been verified in a number of application areas such as elastic analysis [60], fatigue [68,69], fracture mechanics [61,[70][71][72][73], plasticity [74], residual stresses [75], creep [76], variance estimates [77], reliability-based design optimization [78], steady-state thermo-elasticity [79], structural dynamics [80], and periodic material design [81]. However, this is the first demonstration of ZFEM in transient heat transfer problems.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The configuration is taken with the same considerations and initial crack as mentioned above. Crack growth is monitoring using hoop stress, by introducing an additional virtual crack extension (VCE) based on VCE-method Hellen [55], Millwater et al [56] after each equilibrium step. The direction of discrete crack propagation is determined by the orientation in which the maximum energy is released from the system.…”
Section: Numerical Examples Of Thermo-mechanical Analysismentioning
confidence: 99%
“…The complex-valued finite element method is proposed as a new virtual crack extension method to compute the energy release rate (Millwater et al, 2016). Using a complex Taylor series expansion, the energy release rate is obtained as a numerical derivative of the strain energy with respect to a crack extension.…”
Section: Crack Tip Energy Release Ratementioning
confidence: 99%